COMPARISON OF HIGH LEVEL THINKING SKILLS AND BIOLOGY LEARNING OUTCOMES OF STUDENTS WHO LEARNED USING PROBLEM-BASED LEARNING MODEL AND DISCOVERY LEARNING MODEL OF GRADE X IPA STUDENTS AT MAN 2 IN BIMA CITY - Indriani, Irma (Fashluna: Jurnal Pendidikan Dasar dan Keguruan, 2020)
This study employed quasi experiment which aimed at examining high level thinking skills who learned using problem-based learning model and discovery learning model on environmental change and waste recycling. The populations of the study were all learning groups of grade X IPA of the second semester at MAN 2 in Bima city of academic year 2017/2018. Samples were selected by employing purposive sampling technique. Data of the study were collected by using test methods in forms essays test for high level thinking skills. The results of the study reveal than (i) high level thinking skills of grade X IPA students at MAN 2 in Bima city who learned using problem-based learning model is better than the one using discovery learning, (ii) there is a difference between high level thinking skills of grade X IPA students at MAN 2 in Bima city who learned using problem-based learning model is better than the one using discovery learning.